Garantia fundamental do juízo natural e competência penal privativa nos crimes financeiros e de lavagem de capitais - Rebouças, Sérgio Bruno Araújo (2008)
Accoding to legal experts, epecialized crime currently requires preventive and punitive measures at different levels, including changes to the organization and procedures of the penal justice system. The suggestion that federal criminal courts be specialized in the handling of crimes involving the national financial system and the laundering of goods, entitlements and values was eventually approved by the Federal Council of Justice through Resolution #314/20030. The changes implied in the resolution require the redistribution of police reports and preventive and active criminal proceedings within each district along with the conferral of special powers to different courts regarding specific matters. However, the resolution is unconstitutional as it violates the due process of law (articles 96, II, d, in the Brazilian Constitution) as well as the principle of the separation of powers (articles 2 in the Brazilian Constitution). It likewise constitutes a breach of articles 75, sole paragraph, of the Brazilian Procedural Penal Code, as far as the redistribution of lawsuits to specialized courts is concerned. The Supreme Fedral Court, when ruling on Habeas Corpus #88.660/CE, found the resolution to be in harmony with the Constitution, but dd not rule on the legality of the implied redistribution of lawsuits. The methodology of the study consisted of a review of the literature on jurisprudence and a case study.